Adenosine DeaminaseActivity IN p - Thalass emia - AI- Hakeem, T. M.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The activity Â·of adenosine dcaminase enzyn1eÂ· has been investigated in normal and thalassaemic sera. The data obtaiJ1ed were refl cts an elevation of’ the enzyme ctivity in thalassaemic samples compared with those of healthy normal objects. The study was carried out with (6.5)PH value and 37C as ma.x.Lmum temperature. This study was comprehensive to the electrophopretic behavior of the hemolysate serum in a step of electrophoresis analysis of the thalassaemic-and normal hemoglobin.